Laser Ablation Synthesis of Gold Selenides by using a Mass Spectrometer as a Synthesizer: Laser Desorption Ionization Time-of-Flight Mass Spectrometry - Prokeš, Lubomír; Kubáček, Pavel; Peña-Méndez, Eladia Maria; Amato, Filippo; Conde, José Elias; Alberti, Milan; Havel, Josef (Chemistry (Weinheim an der Bergstrasse, Germany), 2016)
Methods for the rapid construction of new chemical motifs have the potential to accelerate the development of nanoscience. The synthesis of new chemical entities by laser ablation has been systematically demonstrated by using mixtures of gold and selenium. The compounds generated are detected by time-of-flight mass spectrometry and, for selected compounds, the structure is investigated by using density functional theory optimization. In total, 67 new gold selenide clusters have been synthesized, demonstrating an unsuspected richness in gold chemistry. Chemical species generated in the gas phase might inspire new routes for the synthesis of novel compounds in the solid state.
Keywords: nanocomposites; gold; laser ablation; mass spectrometry; ionization